ROUTINE USE OF CEREBRAL PROTECTION (FILTER WIRE) DURING CAROTID ARTERY STENTING - S. E. Kassaian M. Salarifar; M. Alidosti; A. M. Haji-Zeinali (Acta Medica Iranica, 2006)
To minimize the risk of embolic events, several protection strategies have been introduced. We have evaluated the short-term outcome of patients who underwent carotid stenting with the routine use of cerebral protection devices. In our center, 36 successful carotid stenting procedures (of 38 attempted) were performed in 37 patients (23 men; age mean [SD] 667 years). Cerebral protection involved distal filter devices (n = 36). The protection device was positioned successfully in 36 of the 38 attempted vessels. Neurologic complications included 1 major stroke and 1 minor stroke and there wasd 1 sudden cardiac death. The rate of stroke or death was 2 for symptomatic lesions and 1 for asymptomatic lesions, and 2 in patients aged < 80 years and 1 in those aged 80 years. Protection device-related vascular complications were mild spasm occurring after 3 procedures (8%) but none led to neurologic complications. There were another four cardiogenic deaths in 30 day follow up. In this uncontrolled study, routine cerebral protection during carotid artery stenting was technically feasible and clinically safe. The incidence of major neurologic complications in this study was lower than in previous reports of carotid artery stenting without cerebral protection.